The Effect of Directed Reading and Thinking Activity (DRTA) Learning Model assisted by Padlet on Learning Motivation and English Reading Comprehension Ability of Grade IX Students at SMP Negeri 5 Kubu - Santikacahya, I Gede Okta; Santyasa, I Wayan; Suartama, I Kadek (Universitas Cokroaminoto Palopo, 2024)
This study aims to analyze the differences in reading comprehension ability and learning motivation between students who follow the Directed Reading and Thinking Activity (DRTA) model assisted by Padlet and students who follow the direct learning model. This research is a quasi-experiment with Non-Equivalent Pretest-Posttest Control Group Design. The population in this study were ninth-grade students of SMP Negeri 5 Kubu in the 2022/2023 academic year consisting of three classes. The sample selection was carried out using Classroom Random Sampling technique and two classes were selected as samples, one class as the experimental group and the other class as the control group. Data collection was carried out using a reading comprehension ability test and a learning motivation questionnaire. The data obtained were analyzed by MANCOVA with initial reading comprehension ability and initial learning motivation as covariates. The results showed that: First, there is a significant difference in reading comprehension ability and learning motivation together between students who follow the DRTA model assisted by Padlet and students who follow the direct learning model. Second, there is a significant difference in reading comprehension ability between students who follow the DRTA model assisted by Padlet and students who follow the direct learning model. Third, there is a significant difference in learning motivation between students who follow the DRTA model assisted by Padlet and students who follow the direct learning model. The implication of this research shows that to improve learning motivation and reading comprehension ability we can use DRTA model learning assisted by Padlet.